1999
DOI: 10.1182/blood.v94.3.1038.415k22_1038_1045
|View full text |Cite
|
Sign up to set email alerts
|

A BCR-ABL Oncoprotein p210b2a2 Fusion Region Sequence Is Recognized by HLA-DR2a Restricted Cytotoxic T Lymphocytes and Presented by HLA-DR Matched Cells Transfected With an Iib2a2 Construct

Abstract: Peptides corresponding to the fusion site in 210 kD BCR-ABL protein b3a2 (p210b3a2) were previously shown to bind to several HLA class I and II alleles. We have found that b3a2 peptide-specific CD4-positive T-helper cells were able to recognize p210b3a2-positive chronic myelogenous leukemia (CML) blasts in a DR4 restricted manner. Until now, there were no reports of b2a2 breakpoint-specific human T-cell responses. Here we show that repetitive stimulation of T lymphocytes with a 17mer peptide covering the fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In patients with haematological diseases, the presence of similar autologous T‐ or natural killer (NK)‐cell mediated anti‐tumour responses has not been consistently demonstrated. In patients with CML and chronic lymphoid leukaemia (CLL), proliferative and cytotoxic T‐cell responses have been observed against the bcr–abl fusion product and against modified CLL cells respectively (Bocchia et al , 1995; Ten Bosch et al , 1995, 1999; Kato et al , 1998; Yasukawa et al , 1998; Yotnda et al , 1998; Buhmann et al , 1999; Chu et al , 2000). In addition, autologous anti‐leukaemic T‐cell or NK cell responses have been generated in vitro against hairy cell leukaemia (HCL) (van de Corput et al , 1999), acute lymphoblastic leukaemia (ALL) (Montagna et al , 1995; Cardoso et al , 1997) and acute myeloid leukaemia (AML) (Archimbaud et al , 1992a; Charbonnier et al , 1999; Choudhury et al , 1999), although a clear immunosurveillance effect has never been demonstrated.…”
mentioning
confidence: 99%
“…In patients with haematological diseases, the presence of similar autologous T‐ or natural killer (NK)‐cell mediated anti‐tumour responses has not been consistently demonstrated. In patients with CML and chronic lymphoid leukaemia (CLL), proliferative and cytotoxic T‐cell responses have been observed against the bcr–abl fusion product and against modified CLL cells respectively (Bocchia et al , 1995; Ten Bosch et al , 1995, 1999; Kato et al , 1998; Yasukawa et al , 1998; Yotnda et al , 1998; Buhmann et al , 1999; Chu et al , 2000). In addition, autologous anti‐leukaemic T‐cell or NK cell responses have been generated in vitro against hairy cell leukaemia (HCL) (van de Corput et al , 1999), acute lymphoblastic leukaemia (ALL) (Montagna et al , 1995; Cardoso et al , 1997) and acute myeloid leukaemia (AML) (Archimbaud et al , 1992a; Charbonnier et al , 1999; Choudhury et al , 1999), although a clear immunosurveillance effect has never been demonstrated.…”
mentioning
confidence: 99%
“…Over 95% CML patients express the fusion product BCR-ABL on their tumor cells that could induce specific T cell responses (4). In last years, several peptides of the BCR-ABL fusion proteins were characterized (4,(21)(22)(23). Recently, Kessler et al and Volpe et al described novel BCR-ABL derived peptides (7,24).…”
Section: Bcr-abl-directed Vaccination Trials In CMLmentioning
confidence: 99%
“…For MHC binding we have used a number of alternative measures of binding affinity, which are currently in common currency. These include radiolabelled 16 , 17 , 18 and fluorescent 19 , 20 , 21 IC 50 values, BL 50 22 , 23 , 24 (half maximal binding level calculated from a mean fluorescence intensity MFI of MHC‐expressing RMA‐S cells) and SC 50 25 , 26 , 27 (the concentration inducing half of the maximal up‐regulating effect calculated in a peptide‐binding stabilization assay), and half‐lives 6 , 28 , 29…”
Section: Jenpepmentioning
confidence: 99%